Pharmacogenomics: Knowledge, attitude and practice among future doctors and pharmacists-A pilot study - Mainul, Haque; Adamu, Yau (Open Science Publishers LLP Inc., 2016)
Rational application of genomics into practice would lead to safer chemotherapy through individualized medicine. The increasing trends of genetic discoveries coupled with increased adoption of pharmacogenomics in developed countries pose challenges to the presence and future healthcare professionals, not only in Malaysia. This research, aimed to assess knowledge, attitude and practice of final-year future healthcare professionals towards pharmacogenomics. A cross-sectional study was conducted by administering self-completed questionnaire (Reliability 0.82) to 247 participants, among which 68.4% responded. More than half were female medical students. The mean knowledge scores in percentage were 57.57±20.2 with a significant difference between the two groups (p = 0.002). Positive attitude, but low practice were observed which differs between pharmacy and medical students, p<0.05. Association between knowledge, attitude and practice, were investigated. The majority has demonstrated good knowledge and attitude towards pharmacogenomics, but with low practice. Studies are required to large sample and to examine barriers to adoption of pharmacogenomics.